Management of the open journal system towards sinta accreditation in the perspective journal of the palembang religious education and training center - Musyaddad (12 Waiheru, 2023)
Open Journal System (OJS) is a widely used platform for managing academic journals. The purpose of this research is to discuss the process of managing OJS towards SINTA accreditation, which is a recognized accreditation system in Indonesia. This research discusses the importance of SINTA accreditation, the OJS management process, and the benefits of accreditation for academic journals. The data collection method was carried out through document review which was carried out by accessing and checking the website address of the Palembang Religious Education and Training Center's perspective journal from 2020 to 2022. The research findings show that the Perspective Journal has published 6 issues, most of the authors come from outside the management agency, most of the partners in the Perspective Journal come from outside the agency and have been indexed by Google Scholar and Scopus, the E-ISSN number of the Perspective Journal has been issued, has been indexed by DOI (Digital Object Identifier), has been indexed by the GARUDA portal and indexed by Google Scholar. It is expected that effective OJS management can contribute significantly to the journal's success in achieving SINTA accreditation.